(untitled) (Sustainability in Debate, 2021)
Objective: Analyze comparatively the sustainability of menus developed by two university restaurants (UR) in the State of Paraná using the water footprint (WF) and the opinion of diners as parameters. Methods: WF was calculated based on 46 menus in each unit and data on diners through questionnaires for 750 people analyzed with Mann Whitney and Pearson’s chi-square. Results: The highest WF averages were from omnivorous menus compared to vegetarians and UR2 had averages higher than UR1. As for the opinion of diners about UR1, there is greater satisfaction with prices, vegetarian options, and greater knowledge about organic and purchases of family farming (FF) products. Conclusions: Therefore, RU1 is closer to the assumptions of a sustainable diet than UR2, but both should review their menus concerning WF and carry out work with diners on food and sustainability.